Pengaruh Kepercayaan Diri Dengan Kecemasan Berbicara Di Depan Umum Pada Mahasiswa Di Kota Bekasi - Nabilah Rahadatul Aisy, Rina; Rahmat Hidayat, Dede (CV RIFAINSTITUT, 2023)
In socializing life through communication on campus for some students is a challenge in itself because it requires good self-confidence to start communicating with others or speaking in public. Public speaking anxiety is a phenomenon that is often experienced by all individuals including students. The purpose of this study was to look at the effect of Self-Confidence on Public Speaking Anxiety in College Students in Bekasi City. This research was conducted with a quantitative approach. The data collection method in this study uses two instruments used in this study, namely the self-confidence scale and the public speaking anxiety scale which are distributed using google formular. The data analysis technique used in this study is simple linear regression with non-parametric analysis. This study is a negative influence between self-confidence and public speaking anxiety in college students in Bekasi, showing the results that there is an influence between the two variables, namely self-confidence and public speaking anxiety in college students in Bekasi city. In the regression test, the value of R square^( 2) is 0.218 (p = 0.02), indicating that the two variables have an influence and have the opposite direction, which means that the higher a person's level of self-confidence, the lower the level of public speaking anxiety that occurs, so the hypothesis is accepted. So one's self-confidence is very influential to reduce the anxiety of public speaking that will occur, if someone has good self-confidence, the lower the level of public speaking anxiety will be.